2015
DOI: 10.1002/mop.29162
|View full text |Cite
|
Sign up to set email alerts
|

Isolation enhancement of a wideband MIMO antenna using floating parasitic elements

Abstract: A Multiple‐input multiple‐output antenna array with two radiating elements having a wide bandwidth is reported in this work. Spatial diversity has been introduced to achieve the diversity gain and the array was kept compact by introducing five parasitic decoupling elements on the bottom of the substrate; each having a length equal to λ/2 at a specific frequency. Each resonant element offers a resonant bandwidth of 1 GHz starting from 3 GHz to 8.5 GHz. Good agreement between the measured and simulated results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…Figure shows the MIMO antenna and surface current distribution (with and without the coupling structure). From Figure (C), (D), it is observed that the effect of mutual coupling is less in antenna due to the parasitic element …”
Section: Isolation Techniquesmentioning
confidence: 99%
“…Figure shows the MIMO antenna and surface current distribution (with and without the coupling structure). From Figure (C), (D), it is observed that the effect of mutual coupling is less in antenna due to the parasitic element …”
Section: Isolation Techniquesmentioning
confidence: 99%
“…Thus, the major problem in MIMO antenna designs is to suppress the mutual coupling while maintaining a compact antenna configuration. Recently, various decoupling methods have been reported in open literature [3][4][5][6][7][8][9][10][11][12][13]. Usually, antenna elements of different types combined in [3,4] can achieve high isolation, yet the MIMO antennas possess different impedance matchings and radiation characteristics between ports.…”
Section: Introductionmentioning
confidence: 99%
“…A tree-like structure extending from the ground is adopted in [5] to cut down the wideband mutual coupling between the radiating elements. By using the parasitic elements, the MIMO antennas in [6,7] achieve isolation enhancement over a wide bandwidth. However, the wideband decoupling methods often make the antennas relatively large in size and complicated in structure.…”
Section: Introductionmentioning
confidence: 99%
“…The Multiple‐Input and Multiple‐Output (MIMO) technology, which employs several antenna elements in one system, is a key technology for wireless communication system . The application of MIMO technology has been regarded as a significant way to improve the reliability and channel capacity of the wireless communication systems without any increase in transmit power or bandwidth . However, due to the spatial limitation of the modern wireless communication devices, the mutual coupling between MIMO antenna elements in the miniature devices could be very strong, which would result in signal distortion seriously .…”
Section: Introductionmentioning
confidence: 99%